2017
DOI: 10.1158/1078-0432.ccr-16-3224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genome-Wide Analysis of Cisplatin-Induced Peripheral Neuropathy in Survivors of Adult-Onset Cancer

Abstract: Purpose Our purpose was to characterize the clinical influences, genetic risk factors, and gene mechanisms contributing to persistent cisplatin-induced peripheral neuropathy (CisIPN) in testicular cancer survivors (TCS). Experimental Design TCS given cisplatin-based therapy completed the validated EORTC QLQ-CIPN20 questionnaire. An ordinal CisIPN phenotype was derived and associations with age, smoking, excess drinking, hypertension, body mass index, diabetes, hypercholesterolemia, cumulative cisplatin dose,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 53 publications
6
77
0
Order By: Relevance
“…Some of these drugs are related to peripheral neuropathy, such as statins or proton pump inhibitors, which are associated with vitamin B12 deficiency , a peripheral neuropathy risk factor. The number of concomitant medications could also be an indirect measurement of the general health status of the patients, which in cisplatin‐treated patients was found strongly associated with the neuropathy (OR, 0.59; p < .0001) .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these drugs are related to peripheral neuropathy, such as statins or proton pump inhibitors, which are associated with vitamin B12 deficiency , a peripheral neuropathy risk factor. The number of concomitant medications could also be an indirect measurement of the general health status of the patients, which in cisplatin‐treated patients was found strongly associated with the neuropathy (OR, 0.59; p < .0001) .…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping was done as described previously (17,18). DNA was extracted from peripheral blood mononuclear cells.…”
Section: Genotypingmentioning
confidence: 99%
“…QC for batch effects was performed using a batch pseudo-GWAS where variants associated with batch pseudo-phenotype (10 genotypic PC-adjusted P < 10 À4 ) were excluded. SNPs and samples passing QC criteria comprised the input set for imputation with EAGLE phasing, performed on the Michigan Imputation Server using the Haplotype Reference Consortium (18)(19)(20). SNPs with imputation R 2 < 0.8, MAF < 0.01, and INFO scores > 1.05 or < 0.3 were excluded.…”
Section: Genotypingmentioning
confidence: 99%
“…However, we previously showed that peripheral sensory neuropathy among TCS is associated with weight gain adjusted for years since treatment (P5.004). 40 Thus, it is possible that TCS with significant neuropathy may not be able to 9%); black/African American, 6 (1.2%); American Indian, 1 (0.2%); more than one race, 9 (1.8%); and declined to answer/other/ unknown, 40 (8.1%).…”
Section: Discussionmentioning
confidence: 99%